Acute massive pulmonary embolism in a patient using clavis panax - İsa Öner Yüksel; Şakir Arslan; Göksel Çağırcı; Akar Yılmaz (KARE Publishing, 2013)
In recent years, the use of herbal combinations, plant extracts or food supplements has increased in our country and all over the world. However, there is not enough data to determine the effective doses of these substances in the composition of herbal preparations, or their effects on metabolism and drug interactions. With the widespread use of herbal combinations, life-threatening side effects and clinical manifestations that arise from them have been reported. Herein we present a case with acute massive pulmonary embolism while using an herbal combination in the context of Tribulus terrestris, Avena sativa and Panax ginseng. A 41-year-old man was admitted to the emergency department with the complaint of sudden onset of dyspnea and syncope. As a result of investigations (blood gases, echocardiography, ventilation-perfusion scintigraphy) he was diagnosed with an acute massive pulmonary embolism. The patient's use of panax did not pose as a risk factor for the pulmonary embolism. He was given thrombolytic therapy and shortness of breath improved. At the pre-discharge the patient was informed of the risks associated with the herbal combination, especially panax. Coumadin was started and he was discharged for the INR checks to come.